453. Frequency of Symptoms and Asymptomatic SARS-CoV-2 Infection in New Orleans, Louisiana. (31st December 2020) - Feehan, Amy K; Fort, Daniel; Diaz, Julia Garcia; Price-Haywood, Eboni; Velasco, Cruz; Sapp, Eric; Pevey, Dawn; Seoane, Leonardo
Abstract: Background: Individuals infected with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) who do not report symptoms throughout the course of infection (asymptomatic) or those who are asymptomatic when they first contract the virus (presymptomatic) are a major public health concern. However, few prevalence studies to date have targeted the question of asymptomatic frequency within a community. Methods: A stratified, random sample of subjects were sent to testing sites to complete a verbal consent, survey, nasopharyngeal swab, and blood draw. Swabs were tested for active viral shedding (PCR) and blood was tested for immunoglobulin G (IgG) specific to SARS-CoV-2. Disease progression and IgG antibody response Results: Of the 2, 640 subjects, 24 (0·9%) were PCR-positive alone, 30 (1·1%) were PCR-positive and IgG-positive, and 129 (4·9%) were IgG-positive alone. Subjects who reported anosmia were 17 times more likely to test positive. Thirty-eight percent of subjects never experienced symptoms despite developing antibodies to the virus, and 75% did not experience symptoms in the early stage of infection. Rates of reported asymptomatic infection and comorbidities statistically significantly increased with age. Conclusion: This is the first randomized study that pairs PCR and IgG serology that addresses asymptomatic SARS-CoV-2 infection, showing a high frequency of asymptomatic disease. More research is needed to clarify differences between symptomatic and asymptomatic disease. Prevalence and outcomes studies of SARS-CoV-2 should include this group. Disclosures: All Authors : No reported disclosures